1995
DOI: 10.1002/jor.1100130117
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tracking measurement in the normal knee

Abstract: Eleven fresh frozen cadaveric knee specimens were mounted in a knee kinematics test device, and normal patellar movements were evaluated with use of an external device for direct measurement of patellar movements. The effects of four different measurement conditions were assessed through alteration of one condition and determination of its effect on patellar kinematics with the use of six specimens. The four conditions included (a) change of the measuring axis from an axis parallel to the central axis of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
2
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 11 publications
7
53
2
1
Order By: Relevance
“…This in vitro experiment confirmed the general pattern of patellar kinematics found in some previous studies, 13,14,20,22,39 with the patella translating medially as the knee starts to flex, then translating progressively laterally from 208 to 908 knee flexion. The kinematic pattern was repeatable between knees and the medial-lateral translation pattern matched data from dynamic measurements obtained previously in vivo.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This in vitro experiment confirmed the general pattern of patellar kinematics found in some previous studies, 13,14,20,22,39 with the patella translating medially as the knee starts to flex, then translating progressively laterally from 208 to 908 knee flexion. The kinematic pattern was repeatable between knees and the medial-lateral translation pattern matched data from dynamic measurements obtained previously in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…12 A number of studies of patellar tracking have been conducted, both in vitro and in vivo. [13][14][15][16][17][18][19][20][21][22][23][24] A range of tracking patterns (reviewed in ref. 17) were reported, probably reflecting the differing methods used.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,11,34,61,63,95 Other studies have found no initial medial movement. 31,76,77 Of the former group, the point at which the medial displacement becomes maximal and the lateral movement begins is highly variable and ranges from 15° to 40° of knee flexion.…”
Section: Normative Datamentioning
confidence: 95%
“…3,4,11,23,30,34,61,63,77,95 Most studies agree that this initial medial tilt is then followed by a lateral tilt as knee flexion continues past 30° to 50°, but the amount of this lateral tilt ranges from 0.7° to 8.2°. 11,30 One study, Goh et al, 25 described the opposite pattern of an initial lateral tilt followed by a medial tilt at 60° to 90° of knee flexion, although they did not measure the first 20° of knee flexion.…”
Section: Normative Datamentioning
confidence: 99%
“…However, the importance of medial ligamentous structures, especially the medial patellofemoral ligament, for patella tracking is well known [20,21]. Although postoperative muscle weakness is a well aired topic, the influence of muscle strength on PF joint kinematics is controversial [21][22][23][24]. We considered that the Values are expressed as mean±SD *P<0.05 Table 2 Comparison of patella shift between pre-and post-operation influence of vastus medialis weakness on PF kinematics in TKA patients is relatively low, compared to a normal knee, because the kinematics were strongly influenced by the design of the prosthesis or its tibio-femoral motion kinematics [25,26].…”
Section: Discussionmentioning
confidence: 99%